High speed transmission of signal level for white light emitting diode (LED) as a transmitter device by using modified phase equalization - Maad Mohsin Mijwil (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Visible light communication (VLC) also known as "Li-Fi", uses standard LEDs to transmit data such as information, images, music, and videos. The first LED was developed in 1927 by Oleg Vladimírovich Lósev (1903-1942), however it was not used in the industry until the 1960s.In this paper, will describe the implementation of Modified Phase Equalization (MPH) on visible white LED lamps signal because it's has slow transition time that severely limits in the communication system data speeds with phase equalization that increases the bandwidth of the LED modulation. Employ two filters with Modified Phase Equalization: first, Complementary (C) filter to combine between all kinds moving signals and second, finite impulse response (FIR) filter to obtain all coefficients that respective. Implementation in two phases: first, frequency 150KHz with number of signals 15000 signals and second, doubling frequency 300KHz with number of signals 30000 signals of LEDs without losing their main functionality as illumination sources.